Christ returns from the jungle : ayahuasca religion as mystical therapy - Blainey, Marc Gordon (SUNY series in transpersonal and humanistic psychology, 2021)
"An in-depth, ethnographic study of the transnational expansion of Santo Daime, a mystical religious tradition organized around sacramental ingestion of the mind-altering ayahuasca beverage. Explores the attraction of unconventional religions in the age of secularization"--